The impact of aerosols on photolysis frequencies and ozone production in Beijing during the 4-year period 2012-2015 - Wenjie Wang; Xin Li; Min Shao; Min Hu; Limin Zeng; Yusheng Wu; Tan, Tianyi (Atmospheric Chemistry and Physics, 2019)
During the period 2012-2015, photolysis frequencies were measured at the Peking University site (PKUERS), a site representative of Beijing. We present a study of the effects of aerosols on two key photolysis frequencies, j((OD)-D-1) and j(NO2). Both j((OD)-D-1) and j(NO2) display significant dependence on aerosol optical depth (AOD; 380 nm) with a non-linear negative correlation. With the increase in AOD, the slopes of photolysis frequencies vs. AOD decrease, which indicates that the capacity of aerosols to reduce the actinic flux decreases with AOD. The absolute values of slopes are equal to 4.2-6.9x10(-6) and 3.4x10(-3) s(-1) per AOD unit for j((OD)-D-1) and j(NO2) respectively at a solar zenith angle (SZA) of 60 degrees and AOD smaller than 0.7, both of which are larger than those observed in a similar, previous study in the Mediterranean. This indicates that the aerosols in Beijing have a stronger extinction effect on actinic flux than absorptive dust aerosols in the Mediterranean. Since the photolysis frequencies strongly depended on the AOD and the SZA, we established a parametric equation to quantitatively evaluate the effect of aerosols on photolysis frequencies in Beijing. According to the parametric equation, aerosols lead to a decrease in seasonal mean j(NO2) by 24% and 30% for summer and winter, respectively, and a corresponding decrease in seasonal mean j((OD)-D-1) by 27% and 33 %, respectively, compared to an aerosol-free atmosphere (AOD = 0). Based on an observation campaign in August 2012, we used a photochemical box model to simulate the ozone production rate (P(O-3)). The simulation results shows that the monthly mean daytime net ozone production rate is reduced by up to 25% due to the light extinction of aerosols. Through further in-depth analysis, it was found that particulate matter concentra-tions maintain a high level under the condition of high concentrations of ozone precursors (volatile organic compounds, VOCs, and NOx), which inhibits the production of ozone to a large extent. This phenomenon implies a negative feedback mechanism in the atmospheric environment of Beijing.